The Bernese Motive and Goal Inventory for Adolescence and Young Adulthood - Gut, Vanessa; Schmid, Julia; Schmid, Jürg; Conzelmann, Achim (Frontiers in Psychology, 2019)
Exercise- and sport-related motives and goals are important motivational factors in promoting exercise and sport among adolescents and young adults. However, at present, there is no well-validated instrument to assess these factors that considers age-specific characteristics. Therefore, the goals of this study were to adapt the existing Bernese Motive and Goal Inventory in exercise and sport for middle-aged adults for use in adolescents and young adults and to examine its psychometric properties. The Bernese Motive and Goal Inventory for adolescence and young adulthood was validated with 2,318 participants aged between 14 to 34 years old. Applying exploratory structural equation modeling, the inventory demonstrated excellent model fit (CFI = .983, SRMR = .014, RMSEA = .040) using 26 items and covering eight motives and goals: Contact, Competition/Performance, Distraction/Catharsis, Body/Appearance, Health, Fitness, Aesthetics, and Risk/Challenge. A cross-validation confirmed the factor structure. Psychometric analyses revealed good reliabilities (CR ≥ .70, AVE ≥ .50, test‐retest reliability: .62 ≤ rtt ≤ .83) and discriminant validity. The factors correlated, in predictable ways, with exercise- and sport-related self-concordance, indicating criterion validity of the inventory. Additionally, metric measurement invariance was supported for activity levels, gender, and age. Overall, the Bernese Motive and Goal Inventory for adolescence and young adulthood is an age-specific, economical, and psychometrically sound questionnaire to assess exercise- and sport-related motives and goals. The inventory can be used in the practical field of exercise and sport promotion (e.g., sport counseling), as well as in research, to better understand the mechanisms and effects of motives and goals in exercise and sport.